Geospatial monitoring and analysis of agricultural drought to identify hotspots and risk assessment for Senegal - Gurjeet Singh; Narendra N. Das; P.V. Vara Prasad (Geography and Sustainability)
Agricultural drought, characterized by insufficient soil moisture crucial for crop growth, poses significant challenges to food security and economic sustainability, particularly in water-scarce regions like Senegal. This study addresses this issue by developing a comprehensive geospatial monitoring system for agricultural drought using the Regional Hydrologic Extremes Assessment System (RHEAS). This system, with a high-resolution of 0.05°, effectively simulates daily soil moisture and generates the Soil Moisture Deficit Index (SMDI)-based agricultural drought monitoring. The SMDI derived from the RHEAS has effectively captured historical droughts in Senegal over the recent 30 years period from 1993 to 2022. The SMDI, also provides a comprehensive understanding of regional variations in drought severity (S), duration (D), and frequency (F), through S-D-F analysis to identify key drought hotspots across Senegal. Findings reveal a distinct north-south gradient in drought conditions, with the northern and central Senegal experiencing more frequent and severe droughts. The study highlights that Senegal experiences frequent short-duration droughts with high severity, resulting in extensive spatial impact. Additionally, increasing trends in drought severity and duration suggest evolving climate change effects. These findings emphasize the urgent need for sustainable interventions to mitigate drought impacts on agricultural productivity. Specifically, the study identifies recurrent and intense drought hotspots affecting yields of staple crops like maize and rice, as well as cash crops like peanuts. The developed high-resolution drought monitoring system for Senegal not only identifies hotspots but also enables prioritizing sustainable approaches and adaptive strategies, ultimately sustaining agricultural productivity and resilience in Senegal’s drought-prone regions.